Cardiovascular risk and pharmacogenetics of statins in Familial Hypercholesterolaemia - Chora, Joana (2022)
Familial hypercholesterolemia is a cardiovascular disease risk condition since its characterized by elevated lipid values since childhood. In this work we stratified CVD risk in a sample of FH patients and the general population and analysed both cohorts in terms of lipid lowering therapy used and attainment of lipid therapeutic target levels. We saw that while the general population has moderate to high CVD risk, FH patients have high to very high CVD risk. Lipid target levels are not being met and the higher risk groups are the worst controlled. Additionally we studied the association between the genotype of specific statin pharmacogenetic relevant SNPs and lipid values after statin treatment and found that APOE rs7412 is associated with higher LDL values after statin treatment and failure to achieve target lipid levels. Predicting the effect of lipid lowering drugs based on the individual’s genetic background allows for appropriate therapeutic strategies, optimizing therapeutic benefits and minimizing toxicity risk in the individual patient.